Distinct role of subunits of the Arabidopsis RNA polymerase II elongation factor PAF1C in transcriptional reprogramming - Obermeyer, Simon; Stöckl, Richard; Schnekenburger, Tobias; Moehle, Christoph; Schwartz, Uwe; Grasser, Klaus D. (Frontiers in Plant Science, 2022)
Transcript elongation by RNA polymerase II (RNAPII) is dynamic and highly regulated, thereby contributing to the implementation of gene expression programs during plant development or in response to environmental cues. The heterohexameric polymerase-associated factor 1 complex (PAF1C) stabilises the RNAPII elongation complex promoting efficient transcript synthesis. In addition, PAF1C links transcriptional elongation with various post-translational histone modifications at transcribed loci. We have exposed Arabidopsis mutants deficient in the PAF1C subunits ELF7 or CDC73 to elevated NaCl concentrations to provoke a transcriptional response. The growth of elf7 plants was reduced relative to that of wildtype under these challenging conditions, whereas cdc73 plants exhibited rather enhanced tolerance. Profiling of the transcriptional changes upon NaCl exposure revealed that cdc73 responded similar to wildtype. Relative to wildtype and cdc73, the transcriptional response of elf7 plants was severely reduced in accord with their greater susceptibility to NaCl. The data also imply that CDC73 is more relevant for the transcription of longer genes. Despite the fact that both ELF7 and CDC73 are part of PAF1C the strikingly different transcriptional response of the mutants upon NaCl exposure suggests that the subunits have (partially) specific functions.